Multitasking competency development based on environmental capital at PT. PLN. Persero - Karim, Ajrun; Purwono, Rudi; Wijoyo, Suparto; Suhariadi, Fendy (Technium Social Sciences Journal, 2024)
PT. PLN Persero had vertically integrated business processes from upstream to downstream, and with the existence of several levels/levels of office, the appropriate competency model is the multiple competency model. Based on the choice of multiple competency models, in general, PT. PLN Persero competency needs are divided into main competencies, role competencies (soft competencies) and field competencies (hard competencies). Multitasking competence was a competency requirement for all position formations at PLN. derived from the vision, mission and corporate values. This study aimed to identify the development of environmental capital-based multitasking competence at PT. PLN Persero. This research was a descriptive study with a qualitative approach combined with a systematic literature review method. The results of the study concluded that the development of environmental capital-based multitasking competence at PT. PLN Persero identified 4 main competencies in PT. PLN Persero, namely achievement orientation, building trust, continuous learning, and customer focus. These four main competencies were identified based on the vision and mission of PT. PLN Persero and 4 corporate values. The preparation of this multitasking competence has taken into account the business scope of PT. PLN Persero based on environmental capital.